A WeChat-based self-compassion training to improve the treatment adherence of patients with schizophrenia in China: Protocol for a randomized controlled trial - Dong, Die; Mu, Ting-Yu; Xu, Jia-Yi; Dai, Jia-Ning; Zhou, Zhi-Nan; Zhang, Qiong-Zhi; Shen, Cui-Zhen (Frontiers in Psychology, 2022)
At present, adherence to antipsychotic treatment is often poor, leading to recurrence of symptoms. This increases the likelihood of the patient experiencing disability and thus, increases the disease burden for the patient, their family and society as a whole. However, to date, there is no clear evidence regarding the effect of medication adherence interventions on outcomes for patients with schizophrenia. Moreover, the traditional intervention methods are limited by manpower and resources in low- and middle-income countries. Recent studies have demonstrated that increasing a patient’s level of self-compassion may improve their treatment adherence. Online mental health care interventions have advantages in terms of feasibility and acceptability for patients with schizophrenia. In this regard, a WeChat-based self-compassion training protocol to improve patient treatment adherence was designed in this study and will be evaluated in the future to determine its impact on patients with schizophrenia.